From Wavelet Analysis to Fractional Calculus: A Review - Emanuel Guariglia; Rodrigo C. Guido; Gabriel J. P. Dalalana (Mathematics, 2023)
In this note, we review some important results on wavelets, together with their main applications. Similarly, we present the main results on fractional calculus and their current applications in pure and applied science. We conclude the paper showing the close interconnection between wavelet analysis and fractional calculus.